Asymptotic Periodicity for Strongly Damped Wave Equations - Lizama-Yanez, C (2013)
This work deals with the existence and uniqueness of asymptotically almost-periodic mild solutions for a class of strongly damped semilinear wave equations. © 2013 Claudio Cuevas et al.